2016
DOI: 10.1016/j.vaccine.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-M adjuvant enhances antibody, cellular and protective immune responses of a Zaire Ebola/Makona virus glycoprotein (GP) nanoparticle vaccine in mice

Abstract: Ebola virus (EBOV) causes severe hemorrhagic fever for which there is no approved treatment or preventive vaccine. Immunological correlates of protective immunity against EBOV disease are not well understood. However, non-human primate studies have associated protection of experimental vaccines with binding and neutralizing antibodies to the EBOV glycoprotein (GP) as well as EBOV GP-specific CD4(+) and CD8(+) T cells. In this report a full length, unmodified Zaire EBOV GP gene from the 2014 EBOV Makona strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 43 publications
6
97
0
Order By: Relevance
“…Notably, clinical trials of VSV-based vaccine 16-17 showed that immunization with GP Kikwit led to production not only Kikwit GP-specific antibodies, but also Mayinga GP and Makona/Gueckedou GP (2014). Animal studies of EBOV-GP nanoparticles showed that mice immunized with GP Makona produced NtAb to ZEBOV Mayinga and were protected from lethal dose of ZEBOV Mayinga 18 . All these data suggest that there is cross-protection from the immune responses to Makona/Gueckedou, Mayinga, and Kikwit.…”
Section: Discussionmentioning
confidence: 88%
“…Notably, clinical trials of VSV-based vaccine 16-17 showed that immunization with GP Kikwit led to production not only Kikwit GP-specific antibodies, but also Mayinga GP and Makona/Gueckedou GP (2014). Animal studies of EBOV-GP nanoparticles showed that mice immunized with GP Makona produced NtAb to ZEBOV Mayinga and were protected from lethal dose of ZEBOV Mayinga 18 . All these data suggest that there is cross-protection from the immune responses to Makona/Gueckedou, Mayinga, and Kikwit.…”
Section: Discussionmentioning
confidence: 88%
“…19, 20 The production of high-affinity class-switched antibodies is dependent on germinal center (GC) formation; 26, 33 however, limited characterization of this B-cell compartment has been reported for vaccine platforms that were developed against EBOV. 28 Therefore, we examined if VLP vaccination resulted in the generation of GC reactions and if poly-ICLC would impact these responses. Mice were vaccinated with VLP (intramuscularly) in the presence or absence of poly-ICLC using a prime-boost schedule at three-week intervals (day 0, day 21).…”
Section: Resultsmentioning
confidence: 99%
“…23, 24, 45 However, little is known about the early EBOV B-cell initiating events that are required for the establishment of these responses. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization experiments using Matrix-M as adjuvant reveal an antigen specific immune response characterized by long-lasting antibody production, a balanced T H 1/T H 2 cytokine profile and induction of cytotoxic T cells [79]. These adjuvant properties of Matrix-M also seem to increase the otherwise poor immunogenicity of Ebola virus glycoproteins [10]. …”
Section: Introductionmentioning
confidence: 99%